A B Cell-Driven Autoimmune Pathway Leading to Pathological Hallmarks of Progressive Multiple Sclerosis in the Marmoset Experimental Autoimmune Encephalomyelitis Model - ’t Hart, Bert A.; Dunham, Jordon; Faber, Bart W.; Laman, Jon D.; van Horssen, Jack; Bauer, Jan; Kap, Yolanda S. (Frontiers in Immunology, 2017)
The absence of pathological hallmarks of progressive multiple sclerosis (MS) in commonly used rodent models of experimental autoimmune encephalomyelitis (EAE) hinders the development of adequate treatments for progressive disease. Work reviewed here shows that such hallmarks are present in the EAE model in marmoset monkeys (Callithrix jacchus). The minimal requirement for induction of progressive MS pathology is immunization with a synthetic peptide representing residues 34-56 from human myelin oligodendrocyte glycoprotein (MOG) formulated with a mineral oil (incomplete Freund’s adjuvant; IFA). Pathological aspects include demyelination of cortical grey matter with microglia activation, oxidative stress and redistribution of iron. When the peptide is formulated in complete Freund’s adjuvant (CFA), which contains mycobacteria that relay strong activation signals to myeloid cells, oxidative damage pathways are strongly boosted leading to more intensive pathology. The proven absence of immune potentiating danger signals in the MOG34-56/IFA formulation implies that a narrow population of antigen-experienced T cells present in the monkey’s immune repertoire is activated. This novel pathway involves the interplay of lymphocryptovirus (LCV)-infected B cells with MHC class Ib/Caja-E restricted CD8+CD56+ cytotoxic T lymphocytes.